Communicating future overheating risks to building design practitioners: Using the Low Carbon Futures tool. (March 2015) - Gul, Mehreen Saleem; Jenkins, DP; Patidar, S; Menzies, GF; Banfill, PFG; Gibson, GJ
The Low Carbon Futures tool provides a probabilistic assessment of future overheating risks and cooling demands for domestic and nondomestic buildings in the UK. The approach adopted for the development of the Low Carbon Futures tool includes academic rigour within the development of the calculation engine, and also practitioner feedback throughout the process. This paper discusses the journey of the tool from modelling and simulation to the practitioner engagement, which took place by means of a questionnaire, focus groups and interviews with building design professionals aimed at understanding how the issue of overheating in buildings is being addressed. Throughout these events, the synergies between designing for low-carbon targets and designing for a future climate were explored. A final dissemination event was held to identify output styles that could be generated by the Low Carbon Futures tool that would be more practical and useful for specific client types. The workshop discussions serve to shape the outputs from the tool, and the feedback gathered will be used to inform a number of output styles, based on client type. Practical application : This paper outlines the development of the Low Carbon Futures tool for analysing overheating risks in buildings and discusses the practitioner feedback obtained from industry professionals on the use and applicability of the tool, in a final event hosted by the Low Carbon Futures research team in London. This event confirmed that practitioners need to be comfortable with the layout and format of the output in order to communicate its meaning and possible implications to a range of clients. A balanced output is required, which conveys some of the complexity of the underlying analysis, but which is easily understood and conveyed to a potentially lay audience.